A modern challenge of polymer physics: Novel ways to study, interpret, and reconstruct chromatin structure. (16th November 2019) - Fiorillo, Luca; Bianco, Simona; Esposito, Andrea; Conte, Mattia; Sciarretta, Renato; Musella, Francesco; Chiariello, Andrea M.
Abstract: The constant development of sophisticated technologies is allowing to dissect three‐dimensional chromatin structure at high resolution level. The tremendous amount of quantitative experimental data available today requires a conceptual framework able to make sense of them. In this perspective, polymer physics offers a key tool to interpret chromatin architecture data and to unveil the basic mechanisms shaping its structure. In the very last years, several polymer models have been proposed and have allowed to capture complex features emerging from the data. The major peculiarity distinguishing the different models is represented by the more or less complicated physical mechanism used to explain chromatin folding. Here, we review very popular models which have been recently developed and which represent brilliant examples from this interdisciplinary research field. In order to highlight the wide range of practical applications they have, we discuss the cases of the murine Pitx1 and the human EPHA4 loci, showing that polymer physics allows to effectively study chromatin structure in different cell lines and to predict the impact of pathogenic structural variants on the genome three‐dimensional architecture. This article is categorized under: Structure and Mechanism > Computational Biochemistry and Biophysics Molecular and Statistical Mechanics > Molecular Dynamics and Monte‐Carlo Methods Theoretical and Physical Chemistry > Statistical Mechanics Abstract : Polymer physics models allow to explore chromatin three‐dimensional structure and explains experimental data.